2021
DOI: 10.1002/wrna.1678
|View full text |Cite
|
Sign up to set email alerts
|

Microexon alternative splicing of small GTPase regulators: Implication in central nervous system diseases

Abstract: Microexons are small sized (≤51 bp) exons which undergo extensive alternative splicing in neurons, microglia, embryonic stem cells, and cancer cells, giving rise to cell type specific protein isoforms. Due to their small sizes, microexons provide a unique challenge for the splicing machinery. They frequently lack exon splicer enhancers/repressors and require specialized neighboring trans-regulatory and cis-regulatory elements bound by RNA binding proteins (RBPs) for their inclusion. The functional consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…In our software, we integrated the eukaryotic linear motif (ELM) database and the NEASE method to specifically address the functional consequences at the exon-level. Additionally, previous work has found that spliced exons less than 250 nt are significantly conserved in terms of length and sequence across vertebrate species [12, 19, 43, 44]. We clustered differential AS genes and exons into three groups based on the length of the corresponding spliced exons: ≤ 51 nt, 52-250 nt, and ≥ 251 nt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our software, we integrated the eukaryotic linear motif (ELM) database and the NEASE method to specifically address the functional consequences at the exon-level. Additionally, previous work has found that spliced exons less than 250 nt are significantly conserved in terms of length and sequence across vertebrate species [12, 19, 43, 44]. We clustered differential AS genes and exons into three groups based on the length of the corresponding spliced exons: ≤ 51 nt, 52-250 nt, and ≥ 251 nt.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that micro-exons exhibit tissue-specific expression patterns and play important roles in cell differentiation, cell migration, neuronal and glial functions [16][17][18]. Mis-regulated micro-exons appear to contribute to the development of neurological disorders and cancer [19]. In our ASTK pipeline, we provide the option to cluster AS genes according to spliced exon lengths before running downstream analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Through AS, hundreds of thousands of RNA isoforms with distinct structural properties, localization patterns, and translation efficiencies can be expressed as protein isoforms with diverse functions [ 9 ]. Moreover, the misregulation of AS has been linked to various diseases, such as central nervous system diseases [ 10 ], heart diseases [ 11 ], carcinoma [ 12 ], immune diseases [ 13 ], and metabolic diseases [ 14 ]. Preexisting studies have also revealed the alternative splicing of VEGF [ 15 ], TUBD1 [ 16 ] in DR.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-binding proteins (RBPs) are vital regulators of an mRNA life cycle, including their transcription, splicing export, and transport to degradation, deadenylation, storage, silencing, and mRNA translation (protein synthesis) [ 17 , 18 ]. Along with the spliceosome complex, RBPs have a major role in creating cell-type-specific regulation of alternative splicing [ 10 , 19 , 20 ]. Previous researchers have revealed the regulatory role of zinc finger RNA-binding protein [ 21 ] and the ELAVL1 (or human antigen R (HuR)) RNA-binding protein [ 22 ] in DR.…”
Section: Introductionmentioning
confidence: 99%
“…Small GTPases contain a diverse set of exons with propensity for alternative splicing that can impact biology, including neurodevelopmental disorders and cancer ( Lee et al, 2022 ). Within cancer, splicing changes in small GTPases have been noted for genes including NRAS , KRAS , HRAS , and RAC1 ( Rásó, 2020 ).…”
Section: Introductionmentioning
confidence: 99%